Healthy Community: Sports massage services for the residents of Ngawi City during Car Free Day - Wargama, I Made Dwi Sastra; Utomo, Andy Widiya Bayu (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2025)
High physical activity among the people of Ngawi City, especially during Car Free Day (CFD), can increase the risk of physical and mental fatigue if not balanced with adequate recovery. To overcome this, the team from STKIP Modern Ngawi organized a community service program in the form of socialization and sports massage practices in the CFD area of Ngawi Square. This activity aims to increase public understanding of the importance of post-physical activity recovery and introduce sports massage as one of the effective methods to maintain fitness. The activity implementation method consisted of preparation, implementation, and evaluation stages. A total of 43 residents from various age groups and educational backgrounds actively participated in this activity. The evaluation results showed that participants felt the direct benefits of sports massage, such as muscle relaxation, improved blood circulation, and a general sense of comfort. In addition, this activity is also a means of education and strengthening student skills in field practice. Sports massage is proven to be an alternative solution in maintaining and restoring public health, and it has the potential to be a business opportunity in the future. In conclusion, this service activity effectively increases public awareness of the importance of maintaining health and fitness through simple, affordable, and applicable methods.